Pelindungan Pekerja Rumah Tangga Migran Perempuan Berdasarkan Asas Keadilan dan Kesetaraan Gender - Najwa Amelia Mumtaz; Febriyani Cahyani Purnomo (Fakultas Hukum Universitas Islam Indonesia, 2025)
Female migrant domestic workers often experience gender injustice and inequality. This is due to the patriarchal paradigm and the feminization of migration in society. This condition is of course very dangerous in the midst of the large number of female migrant domestic workers. This research will examine the government's policy in protecting female migrant domestic workers in relation to the principles of justice and gender equality and a comparison of the regulation of the protection of female migrant domestic workers between Indonesia and the Philippines. This type of research is normative juridical research through statute approach, conceptual approach, and comparative approach. The results show that Law No. 18/2017 on the Protection of Indonesian Migrant Workers and the Draft Law on the Protection of Indonesian Migrant Workers have not accommodated the specific needs of female migrant domestic workers as a vulnerable group based on the principles of gender equality and justice, while the Philippines through Batas Kasambahay has provided guarantees for the basic rights of domestic workers.